Auditoría de los rubros: ingresos, cuentas por cobrar y activo fijo a una empresa que se dedica a la importación y comercialización de focos y lámparas, en la ciudad de Guayaquil, por el período terminado el 31 de diciembre del 2007 - Acuña Cantos, Diego Daniel (2011)
The present work has the purpose to make a analysis of the items: Income, Accounts Receivable and Fixed Assets of a company dedicated to the import and sale of light bulbs and lamps, in the city of Guayaquil, for the period ended on 31 December 2007. The purpose is to express an opinion about these items if they are presented fairly, in accordance with International Accounting Standards. Chapter I presents the theoretical framework, concepts and definitions that form the basis upon which we will measure the items and its reasonable presentation. Chapter II lays out a plan to develop it, the stages of analysis that include things like understanding of the business sector in which it operates, the nature of transactions, accounting procedures and principles followed by the company, as well as compliance with levels of control. In Chapter III, the practical tests of accounting information are develop, procedures guided principally to analyzing and testing about off-balance sheet accounting records. Chapter IV presents the conclusions and recommendations arising from the analysis, results of tests given and applied.